Approach to and Practice of Disc Fenestration in the Management of Intervertebral Disc Extrusions in Dogs: A Questionnaire Survey - Hall, Jessica Falconer; Freeman, Paul (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective Intervertebral disc fenestration has been shown to reduce the risk of extrusion in the thoracolumbar region in dogs, but use of the technique varies between individual neurologists and surgeons. Our aim was to investigate opinions and practices regarding disc fenestration amongst those involved in neurosurgery in dogs.Study Design A web-based survey containing questions relating to the use of fenestration during treatment of intervertebral disc extrusion in dogs was distributed to board-certified neurologists and surgeons. Results were analysed using Microsoft Excel.Results There were 323 responses from 190 neurologists and 133 surgeons. Seventy-one per cent of respondents routinely used concurrent disc fenestration when performing decompressive surgery in the thoracolumbar region, although the rate was lower amongst surgeons (55%) than neurologists (82%). Only 25% of respondents performed concurrent fenestration in the cervical spine. Forty-five per cent of respondents reported having experienced complications, with haemorrhage being the most common.Conclusion Fenestration is widely used in the management of thoracolumbar intervertebral disc extrusion, but a universally accepted approach does not exist, and differences are seen between neurologists and surgeons.
Keywords: fenestration; intervertebral disc extrusion; neurosurgery; extrusion; dog